Pleurotus eryngii Genomes Reveal Evolution and Adaptation to the Gobi Desert Environment - Dai, Yueting; Sun, Lei; Yin, Xiaolei; Gao, Meng; Zhao, Yitong; Jia, Peisong; Yuan, Xiaohui; Fu, Yongping; Li, Yu (Frontiers in Microbiology, 2019)
Pleurotus eryngii (King Oyster) is one of the most highly prized edible mushrooms. Among the diverse varieties within P. eryngii, P. eryngii var. eryngii is the commonest one, with a worldwide distribution, while P. eryngii var. ferulae is only distributed in Europe and China, and is especially adapted to the Gobi Desert in Xinjiang Autonomous Region of China. However, little is known about the genome-wide pattern of evolution and adaptation to the divergent environments of P. eryngii. Here, we present the high-quality genome sequences of P. eryngii var. eryngii strain PEE81 originating from Europe and P. eryngii var. ferulae strain PEF12 originating from the Gobi Desert of China. The assembled genome sizes of PEE81 and PEF12 were 53.6 and 48.0 Mbp, respectively, which are larger than other reported genomes in the genus Pleurotus. We propose that the selective amplification of long terminal repeat (LTR) retrotransposons increases the genome size of the genus Pleurotus, and may play a key role in driving their rapid species diversification. Molecular clock analyses of five Pleurotus species, namely PEE81, PEF12, P. tuoliensis, P. ostreatus and P. cf. floridanus suggest that the divergence estimates of the genus Pleurotus over time scales ranged from ∼4 to ∼38 million years ago (Mya), and PEE81 and PEF12 diverged at ∼13 Mya. The whole genome resequencing of 33 geographically diverse strains of P. eryngii var. eryngii and var. ferulae was then performed and the genome variation among and within these two populations were investigated. Comparative analyses of these two populations detected several candidate genes related to stress responses and DNA repair that are putatively involved in adaptation to the Gobi Desert environment. These findings offer insights into genome evolution of the genus Pleurotus and provide valuable genomic resources for King Oyster mushroom breeding.